Equations » Logarithmic equations

ln(x) = elog(x) with  e = 2.71828182846...

Check logarithm rules if needed too.

Example 1
3log(x – 2) = 1 + 4 · 3log(2)
3log(x – 2) = 3log(3) + 3log(24)
3log(x – 2) = 3log(3) + 3log(16)
3log(x – 2) = 3log(3 · 16)
3log(x – 2) = 3log(48)
x – 2 = 48
x = 50

Example 2
1 + 2 · 2log(x= 2log(5x + 3)
2log(2) + 2log(x2= 2log(5x + 3)
2log(2x2= 2log(5x + 3)
2x2 = 5x + 3 
2x2 – 5x – 3 = 0 
D = (–5)2 – 4 · 2 · –3 = 49
x = –(–5) + wortel 492 · 2 or x = –(–5) – wortel 492 · 2
x = 3 or x = –12

Example 3
0.5log(x + 6) + 2 · 2log(x= 0
2log(x + 6) + 2log(x2= 0
2log(x + 6) = –2log(x2)
x + 6 = x2
x2 + x + 6 = 0
x2 – x – 6 = 0
(x + 2)(x – 3) = 0
x = –2 or x = 3

As x = –2 is not a solution to the original equation, the correct solution is only x = 3.

Example 4

(3log(x) )2 – 3log(x) = 0
Substitute: p = 3log(x)

p2 – p = 0 
 p(p 1) = 0 
p = 0 or p = 1
3log(x) = 0 or 3log(x) = 1
x = 1 or x = 3

Example 5
4log(x= 2log(x – 2)
2log(x)2log(4) = 2log(x – 2)
2log(x)2 = 2log(x – 2)
2log(x= 2 · 2log(x – 2)
2log(x= 2log( (x – 2)2 )
x = (x – 2)2
x = (x – 2)(x – 2)
x = x2 – 4x + 4
= x2 – 5x + 4
= (x – 1)(x – 4)
  x = 1 or x = 4

As x = 1 is not a solution to the original equation, the correct solution is only x = 4.